Deletion Polymorphism of UDP-Glucuronosyltransferase 2B17 and Risk of Prostate Cancer in African American and Caucasian Men - Jong Park; Lan Chen; Luke Ratnashinge; Thomas A. Sellers; Jean-Paul Tanner; Ji‐Hyun Lee; Nicole Dossett; Nicholas P. Lang; Fred F. Kadlubar; Christine B. Ambrosone; Babu Zachariah; Randy V. Heysek; et al. (2006)
Abstract Purpose: UDP-glucuronosyltransferases (UGT) are a family of enzymes that glucuronidate many endogenous chemicals, including androgens. This makes them more hydrophilic, alters biological activity, and facilitates their excretion. A deletion polymorphism in the UGT2B17 gene was recently described that was associated with a reduced rate of glucuronidation in vivo. The purpose of this study was to determine if the deletion polymorphism is associated with susceptibility to prostate cancer. Materials and Methods: UGT2B17 expression was determined by reverse transcription-PCR of pathologically normal prostate tissues (n = 5). In a case-control study with 420 patients with incident primary prostate cancer (127 African Americans and 293 Caucasians) and 487 controls (120 African Americans and 367 Caucasians), the frequency of UGT2B17 deletion polymorphism in genomic DNA was compared between cases and controls with PCR analysis. Results: UGT2B17 mRNA was detected only in individuals with at least one UGT2B17 allele. The frequency of the null genotype was present in 0.11 and 0.12 of Caucasian and African American controls, respectively. When all subjects were considered, a significant association was found between the UGT2B17 deletion polymorphism and prostate cancer risk [odds ratio (OR), 1.7; 95% confidence interval (95% CI), 1.2-2.6]. There was an increase in prostate cancer risk among individuals with UGT2B17 deletion polymorphism in Caucasians (OR, 1.9; 95% CI, 1.2-3.0) but not in African Americans (OR, 1.3; 95% CI, 0.6-2.7). Conclusions: These results suggest that the UGT2B17 enzyme may play a role in the metabolism of androgens in prostate tissue and that the UGT2B17 deletion polymorphism is associated with prostate cancer risk. (Cancer Epidemiol Biomarkers Prev 2006;15(8):1473–8)